Functional integration within the human pain system as revealed by Granger causality - Ploner, Markus (Hum Brain Mapp, 2009)
Pain is a complex experience subserved by an extended network of brain areas. However, the functional integration among these brain areas, i.e., how they interact and communicate to generate a coherent pain percept and an adequate behavioral response is largely unknown. Here, we used magnetoencephalography to investigate functional integration among pain‐related cortical activations in terms of Granger causality and compared it with tactile‐related activations. The results show causal influences of primary somatosensory cortex on secondary somatosensory cortex for tactile‐related but not for pain‐related activations, which supports the proposition of a partially parallel organization of pain processing in the human brain. Furthermore, during a simple reaction time task, the strength of causal influences between somatosensory areas but not the latencies between activations correlated significantly with the speed of reaction times. These findings show how the analysis of functional integration complements traditional analyses of electrophysiological data and provides novel and behaviorally relevant information about the organization of the human pain system. Hum Brain Mapp, 2009. © 2009 Wiley‐Liss, Inc.